2005
DOI: 10.1097/01.pcc.0000163678.20704.c5
|View full text |Cite
|
Sign up to set email alerts
|

Steroid use before pediatric cardiac operations using cardiopulmonary bypass: An international survey of 36 centers*

Abstract: Although nearly all centers surveyed administer steroids before cardiopulmonary bypass, the type, dosing, route, and timing of administration are highly variable. The inconsistencies in these data and the pediatric literature would support the undertaking of a large, multiple-center clinical trial to evaluate the risks and benefits of steroid administration before pediatric cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
87
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 27 publications
4
87
1
4
Order By: Relevance
“…20 However, more recent analyses of large data sets have shown that there is in fact widespread variation in the way corticosteroids are used in this setting, and have questioned the clinical benefit associated with corticosteroids. 1,6 These data support the feasibility and necessity of a large randomized trial.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…20 However, more recent analyses of large data sets have shown that there is in fact widespread variation in the way corticosteroids are used in this setting, and have questioned the clinical benefit associated with corticosteroids. 1,6 These data support the feasibility and necessity of a large randomized trial.…”
Section: Discussionsupporting
confidence: 53%
“…Corticosteroids are administered to patients undergoing heart surgery with the aim of attenuating the systemic inflammatory response and capillary leak syndrome that can be triggered by cardiopulmonary bypass. 1,16,17 Although numerous studies have reported that corticosteroids are effective at reducing levels of certain inflammatory markers in this setting, mounting evidence questions the benefit of corticosteroids in relation to clinical outcomes. 5,6,8 Inarecentmeta-analysis, corticosteroids were not associated with any difference in duration of ventilation or LOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available data suggest a clinical benefit of steroid application, but many details are unknown and conditions of steroid administration are highly variable (15). Evidence from adult trials is conflicting regarding the effects of GC on postoperative outcome such as postoperative course, length of hospital stay and survival (14,17).…”
mentioning
confidence: 99%
“…One of these strategies is the pre-or intraoperative application of glucocorticoids (GC). These steroids have an anti-inflammatory action (13), therefore steroid derivatives such as methylprednisolone (MP) or dexamethasone have been widely used during CPB surgery (14,15). MP also has a protective effect on the vascular endothelium during cardiovascular surgery (16).…”
mentioning
confidence: 99%